Obesidad pregestacional y riesgo de diabetes gestacional. Hospital Provincial General Docente Riobamba, 2014 – 2019.” - Garcés Vallejo, Carol Kelly (2021)
ABSTRACT Introduction: In Ecuador, it has been evidenced that the prevalence of gestational diabetes is 8% and is the cause of several maternal and neonatal complications. It is considered that approximately 150 to 1000 cases occur per 100,000 inhabitants. These figures are alarming since most pregnant women do not present symptoms and, for this reason, go unnoticed, it is essential to carry out prenatal control and, above all, universal screening for this pathology within 24 to 28 weeks. Objective: To determine the risk of developing gestational diabetes in obese pregnant women admitted to the Riobamba Provincial General Teaching Hospital during 2014 - 2019. Methodology: a descriptive, retrospective, cross-sectional study was carried out, with a quantitative approach, using inclusion criteria and exclusion; the sample was 397 patients. Results: From the sample's total, 34 patients are obese pregnant women with gestational diabetes. The most affected age group was 15 to 35 years old with 59%, 50% belonged to the mixed ethnic group, the patients with a history of gestational diabetes corresponded to 35%, the pregnant women with a history of macrosomic delivery belong to the 21%. Conclusions: The most affected population was obese pregnant women between 15 and 35 years of age. Keywords: Pregnancy, prenatal control, gestational diabetes, obesity, macrosomic births.